Social Accountability of Microfinance Institutions in South Asian Region - Ahmed, Iftekhar; Bhuiyan, Abul Bashar; Ibrahim, Yusnidah; Said, Jamaliah; Salleh, Mohammed Fuad Mohd (International Journal of Economics and Financial Issues, 2016)
The purpose of the study is to examine the social accountability and argue comparison of outreach level of microfinance institutions in member countries of South Asian Association for Regional Cooperation (SAARC). The inquiry has employed quantitative research approach to meticulous secondary data that has quantify using financial ratio and multiple regression analysis. Our results expose that gross loan portfolio has significant positive relation with the number of clients served. Conversely, the average loan balance per borrower per GNI per capital and average outstanding balance have significant negative relation to the dependent variable. On the other hand, the yield on a gross loan portfolio, size of MFI and operational self-sufficiency has insignificant effect to the number of active borrowers. Eventually the study found no evidence of trade-off between profitability and outreach breadth. However, interest rate, board and ownership structure and outreach depth issue suggested for the further studies. Keywords: Microfinance, Accountability, Outreach, Mission Drift, South Asia JEL Classifications: G21, G32, O18